Oxidative and modulatory effects of trace metal on metabolism of polycyclic aromatic hydrocarbons in the antarctic fish Trematomus bernacchii - BENEDETTI, MAURA; MARTUCCIO G; FATTORINI, DANIELE; CANAPA, Adriana; BARUCCA, MARCO; NIGRO M; REGOLI, Francesco (Aquatic Toxicology, 2007)
Biological interactions between various classes of pollutants are of great relevance for the Antarctic marine environment, where the naturally elevated bioavailability of metals like cadmium might indirectly influence sensitivity of endemic organisms toward other environmental pollutants, e.g. polycyclic aromatic hydrocarbons (PAHs). To further investigate reciprocal effects of different chemicals, the fish Trematomus bernacchii was exposed to trace metals (Cd, Cu, Hg, Ni, Pb) and benzo[a]pyrene (BaP, as a model PAH), dosed alone and in combinations. Co-exposures revealed that BaP did not influence the accumulation of metals, while these elements caused significant changes on tissue levels of the PAH. The marked EROD induction caused by BaP was completely suppressed by co-exposure with Cd and Cu, but no effects were observed with Ni, Hg and Pb. Similar results were confirmed at the protein level by Western blot analyses while CYP1A1 mRNA levels were reduced only during Cd co-exposures. Clear evidence of oxidative perturbations was observed in fish co-treated with Cd and BaP and the reduced capability to absorb peroxyl and hydroxyl radicals suggested some oxidative pathways by which this element might indirectly modulate the biotransformation efficiency of Cytochrome P450. Partly different and post-transcriptional mechanisms of action could be hypothesized for Cu, while moderate oxidative effects of Hg, Ni and Pb during co-exposures would confirm their limited influence on metabolism of PAHs. In general, the overall results revealed a complex pathway of interactions between different chemicals during co-exposures and the importance of oxidative status in modulating induction and expression of CYP1A1.